Mini invasive coronary artery bypass grafting: a case report - B. Todurov; A. Bitsadze; М. Glagola; А. Ivanuk; V. Demyanchuk (Ukrainian Journal of Cardiovascular Surgery, 2016)
Standard access in surgical myocardial revascularization in patients with coronary heart disease is traditionally a longitudinal median sternotomy. In order to minimize surgical trauma, length of hospitalization and rehabilitation of the operated patients are now more widely used minimally invasive approaches. We present a clinical case of a successful coronary bypass surgery performed in 57-year-old patient using mini sternotomy.